The Good, the Bad and the Unknown Aspects of Ghrelin in Stress Coping and Stress-Related Psychiatric Disorders - Fritz, Eva Maria; Singewald, Nicolas; De Bundel, Dimitri (Frontiers in Synaptic Neuroscience, 2020)
Ghrelin is a peptide hormone released by specialized X/A cells in the stomach and activated by acylation. Following its secretion, it binds to ghrelin receptors in the periphery to regulate energy balance, but it also acts on the central nervous system where it induces a potent orexigenic effect. Several types of stressors have been shown to stimulate ghrelin release in rodents, including nutritional stressors like food deprivation, but also physical and psychological stressors such as foot shocks, social defeat, forced immobilization or chronic unpredictable mild stress. The mechanism through which these stressors drive ghrelin release from the stomach lining remains unknown and, to date, the resulting consequences of ghrelin release for stress coping remain poorly understood. Indeed, ghrelin has been proposed to act as a stress hormone that reduces fear, anxiety- and depression-like behaviors in rodents but some studies suggest that ghrelin may – in contrast - promote such behaviors. In this review we aim to provide a comprehensive overview of the literature on the role of the ghrelin system in stress coping. We discuss whether ghrelin release is more than a byproduct of disrupted energy homeostasis following stress exposure. Furthermore, we explore the notion that ghrelin receptor signaling in the brain may have effects independent of circulating ghrelin and in what way this might influence stress coping in rodents. Finally, we examine how the ghrelin system could be utilized as a therapeutic avenue in stress-related psychiatric disorders (with a focus on anxiety- and trauma-related disorders), for example to develop novel biomarkers for a better diagnosis or new interventions to tackle relapse or treatment resistance in patients.